IDENTIFICATION OF LEAD (Pb) IN WATER SPINACH (Ipomoea aquatica forsk) IN PALLEKO SUB-DISTRICT NORTH POLONGBANGKENG TAKALAR REGENCY - Rahmawati, Rahmawati; Aziz, Nurul Ni’ma; Nurhidayat, Nurhidayat; Salzabila, Awalia (Media Kesehatan Politeknik Kesehatan Makassar, 2022)
The sugar factory located in Palleko Village can produce air pollution and waste which is suspected to pollute the environment and waters. Environmental pollution in the form of lead metal can contaminate water and soil around industrial plants. Environmental pollution in water is thought to be higher than on land because it is polluted from mining processes and industrial waste. Lead metal is thought to be able to contaminate plants in water, for example kale, which is a mediator of the spread of heavy metals in living things due to the entry of these metals into plants through roots and leaf mouths (stomata). Water spinach that grows around industrial factories is at risk of being exposed to pollutant substances such as lead (Pb). Lead consumed can cause symptoms of chronic poisoning, paralysis, can affect the circulatory system, nervous system, urinary system. This study aims to identify lead (Pb) in water spinach (Ipomoea aquatica forsk) in Palleko Village, North Polongbangkeng District, Takalar Regency. This research was conducted by laboratory observation with purposive sampling technique using the color reaction test as many as 9 samples. The results showed that of the 9 samples of water spinach (Ipomoea aquatica forsk) examined, the results were all negative for lead metal. it was concluded that water spinach does not contain lead so it is safe for consumption according to the Decree of the Director General of Drug and Food Control Number 03725/B/SK/VII/89 concerning the maximum limit of metal contamination in food is 2.0 mg/kg.